THE EFFECT OF ENVIRONMENT AND LEARNING STYLE ON STUDENTS' PERFORMANCE THROUGH MOTIVATION AS A MODERATOR VARIABLE - Asyhar, Wildan Isna; Firadiba, Charisma (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2023)
This research aims to interpret the research analysis: (1) to know the simultaneous effect of environment, learning style, and motivation on students' performance; (2) to know the partial effect of environment, learning style, and motivation on students' performance; (3) to know the significant effect of environment and learning style partially on students' performance through motivation as a moderator variable. This research used the quantitative approach as the research design and involved 218 students of the tenth grade of MAN 1 Mojokerto as a sample. The data was collected by using a questionnaire. These results showed that: (1) There is a simultaneous effect of environment, learning style, and motivation on students' performance which f- count is 53,333 > f- table 3,177. (2) There is a partial effect of environment, learning style, and motivation on students' performance (3) The indirect effect of environment and learning style is more significant than the direct effect. The conclusion is that the Ho of each hypothesis is rejected.